2022
DOI: 10.1177/09544070221076217
|View full text |Cite
|
Sign up to set email alerts
|

Research on optimal driving behavior decision method based on multi-objective optimization

Abstract: Aiming at the coupling of traffic laws and traffic participants in the current smart car decision-making process, and the lack of systematic processing of traffic laws, this paper proposes an optimal driving behavior decision-making method based on multi-objective optimization. This paper uses a multi-objective optimization method to establish macro path following indicators, collision risk indicators, traffic efficiency evaluation indicators, and driving burden evaluation indicators to solve the problem of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the distribution of lane flow does not typically have a minimum or maximum value, instead, its value fluctuates in tandem with traffic demand [ 6 ]. A multitude of scholars has delved into the study of driving behavior and its consequential impact on traffic, including parameters of driving behavior under specific circumstances [ 7 ] and lane parameters [ 8 ]. Studies conducted on free-flow speed and fundamental patterns under non-congested conditions have demonstrated that road characteristics, including road capacity, heavily rely on driver behavior and are likely to evolve over time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the distribution of lane flow does not typically have a minimum or maximum value, instead, its value fluctuates in tandem with traffic demand [ 6 ]. A multitude of scholars has delved into the study of driving behavior and its consequential impact on traffic, including parameters of driving behavior under specific circumstances [ 7 ] and lane parameters [ 8 ]. Studies conducted on free-flow speed and fundamental patterns under non-congested conditions have demonstrated that road characteristics, including road capacity, heavily rely on driver behavior and are likely to evolve over time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%